Pornography—Is It Good for Sexual Health? A Systematic Review - Saira Hakkim (Journal of Psychosexual Health, 2022)
Aim: The topic of pornography use is controversial. It is important to understand how young people use pornography and determine whether pornography use has adverse effects on health and well-being. Methods: A comprehensive systematic literature search was conducted in 4 electronic databases (PubMed, Google Scholar, CINAHL plus, and Cochrane library) with appropriate MeSH terms “sexual health” and “pornography” and Boolean operators “AND” and “OR,” using SPIDER search strategy tools (sample, phenomenon of interest, design, evaluation, and research type). 11 articles were proceeded with systematic review after critical appraisal following PRISMA guidelines. Results: The major findings of the study imply that traditional and unimaginative activities depicted in some pornography and sexualized media are harmful because they impose restricted and circumscribed concepts of sex and sexuality. As a result, sexism, sexual objectification, neoliberal sexual consumerism, and sexual variety are reproduced and reinforced rather than promoted. FPU is linked to better levels of sexual comfort and self-acceptance and reduced levels of anxiety, shame, and guilt over sexual behavior. Pornography consumption has also been linked to increased arousal and orgasm responses, a greater interest in sex, acceptance of various sexual acts, and more sexual experimentation. Conclusion: Watching pornography may be a healthy phenomenon if it is occasional, not impairing the personal and social life; however, it can become pathological if watched excessively and impairs the individual’s functioning.